Hybrid Implementation Effectiveness Trial: Home-based Intensive Family Coaching to Improve Outcomes for Medicaid-enrolled Preschoolers. Issue 2 (3rd April 2021) - Herschell, Amy D.; Shaffer, Sherry L.; Wallace, Nancy M.; Maise, Amanda A.; Schaffner, Kristen F.; McNeil, Cheryl B.; Dotson, Pamela; Johnson, Virginia J.
ABSTRACT: Despite the prevalence and persistence of behavioral disorders among young children and availability of evidence-based treatments, several barriers prevent families from accessing effective treatments in their communities. This study, which included a hybrid research model, explored the implementation of Intensive Family Coaching (IFC), an adaptation of one evidence-based practice, Parent-Child Interaction Therapy (PCIT). IFC was designed to improve access and reduce attrition by providing services in home and community settings through wraparound services. The findings suggest that although families who engaged in IFC saw significant reduction in child problem behavior, family attrition and staff turnover presented barriers to ongoing implementation.